2016
DOI: 10.1155/2016/4648287
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Biopharmaceutical Characterization of Electrospun PVP Mats with Propolis and Silver Nanoparticles for Fast Releasing Wound Dressing

Abstract: Antibacterial, antiviral, antifungal, antioxidant, anti-inflammatory, and anticancer activities of propolis and its ability to stimulate the immune system and promote wound healing make it a proper component for wound dressing materials. Silver nanoparticles are recognized to demonstrate strong antiseptic and antimicrobial activity; thus, it also could be considered in the development of products for wound healing. Combining propolis and silver nanoparticles can result in improved characteristics of products d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 30 publications
0
9
0
3
Order By: Relevance
“…In the case of the reduction of microbial growth due to the pure PVP fibers presence is confirmed by Adomavičiūtė et al [99]. It was reported that PVP fibers prepared with PEE solvent presented certain bioactivity against Candida albicans ATCC 10231, Bacillus subtilis ATCC 6633 and Bacillus cereus ATCC 11778.…”
Section: Discussionmentioning
confidence: 76%
“…In the case of the reduction of microbial growth due to the pure PVP fibers presence is confirmed by Adomavičiūtė et al [99]. It was reported that PVP fibers prepared with PEE solvent presented certain bioactivity against Candida albicans ATCC 10231, Bacillus subtilis ATCC 6633 and Bacillus cereus ATCC 11778.…”
Section: Discussionmentioning
confidence: 76%
“…Microfibers In Vitro. Samples of acceptor phase used in determination of released silver nanoparticles were filtered through polyvinylidene chloride filter, and chromatographic quantification of vanillin and vanillic, caffeic, p-coumaric, and ferulic acids was performed applying the earlier developed and validated method [17]. Propolis phenolic compounds (vanillic, caffeic, p-coumaric, and ferulic acids and vanillin) were quantified in propolis extracts and samples using Agilent 1260 Infinity Capillary LC (Agilent Technologies, Inc., Santa Clara, CA, USA) with Agilent diode array detector (DAD).…”
Section: Release Studies Of Propolis Phenolic Acids From Electrospunmentioning
confidence: 99%
“…Samples in Mueller-Hinton agar were incubated at 36 ∘ C for 24 h (for bacteria) and at 30 ∘ C for 24 h (for fungi). Samples from nonwoven materials of PLA microfibers with AgNPs antimicrobial activity were determined by the sterile area of the sample [17,18].…”
Section: Preparation Of Investigativementioning
confidence: 99%
“…Oldoni et al (2011) produziram EEP vermelha de origem brasileira, observando a atividade antibacteriana frente à S. aureus, indicando o produto como antioxidante e antimicrobiano para a indústria alimentícia.Atualmente, diversos trabalhos têm demonstrado o uso da própolis associada aos biomateriais, visando a obtenção de um dispositivo que possa ser utilizado no meio biológico e também apresente características antimicrobianas. Neste sentido, o biomaterial contendo a própolis atuaria como sistema de liberação de antimicrobianos in situ(ADOMAVICIUTE et al, 2016;ALTUNSOY et al, 2016;DE LIMA et al, 2016;HATUNOGLU et al, 2014; OLIVEIRA et al, 2015) Há um grande interesse, tanto dos pesquisadores, como da indústria, em desenvolver um biomaterial que apresente características antimicrobianas de alta qualidade e com segurança para o paciente (KENAWY; WORLEY;BROUGHTON, 2007). Desta forma, alguns polímeros têm apresentado grande interesse, devido ao baixo custo de produção e vasta área de aplicação(STRATTON et al, 2010;STRATTON;RICKUS;YOUNGBLOOD, 2009).…”
unclassified
“…Desta forma, alguns polímeros têm apresentado grande interesse, devido ao baixo custo de produção e vasta área de aplicação(STRATTON et al, 2010;STRATTON;RICKUS;YOUNGBLOOD, 2009). Neste sentido, a própolis tem sido associada a biopolímeros visando melhora nas propriedades físicas, aliada a atividade antimicrobiana do produto final(ADOMAVICIUTE et al, 2015;ADOMAVICIUTE et al, 2016;DE LIMA et al, 2016;KIM et al, 2014; OLIVEIRA et al, 2015;SUTJARITTANGTHAM et al, 2014).Adoma viciute et al (2016) utilizaram a técnica de eletrospinning para produzir material utilizado como curativo de feridas de polivinilpirrolidona (PVP), contendo extrato de própolis e nanopartículas de prata. Os resultados demostraram rápida liberação de fenólicos e maior atividade antibacteriana contra S. aureus e E. coli para as amostras contendo prata.…”
unclassified